Structure & function of the body - Thibodeau, Gary A. (Elservier/Mosby, 2012)
Simple and straightforward, Thibodeau and Patton's Structure & Function of the Body, 14th Edition makes the difficult concepts of anatomy and physiology clear and easier to understand. Focusing on the normal structure and function of the human body and what the body does to maintain homeostasis, this introductory text provides more than 400 vibrantly detailed illustrations and a variety of interactive learning tools to help you establish an essential foundation for success in the care of the human body.